Gender-related differences in disease activity and clinical features in patients with peripheral psoriatic arthritis: A multi-center study - GEZER, HALİSE HANDE; DURUÖZ, MEHMET TUNCAY; ACER KASMAN, SEVTAP (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2021)
Objective: This study sought to compare disease activity, clinical features, and patient-reported outcomes concerning anxiety, depression, fatigue, function, quality of life, and fibromyalgia between female and male patients with peripheral PsA in a Turkish population. Methods: This multi-center Turkish League Against Rheumatism (TLAR) Network study included 1038 patients (678 females, 360 males) diagnosed with peripheral PsA according to the CASPAR criteria. The demographic and clinic parameters of the patients were recorded. Disease activity was evaluated using the scores of DAS28 and cDAPSA. Remission, minimal disease activity (MDA), and very low disease activity (VLDA) were determined. Health Assessment Questionnaire (HAQ), Short-Form-36 (SF-36), Hospital Anxiety and Depression Scale (HAD), fatigue VAS (0-10), and Fibromyalgia Rapid ScreeningTool (FiRST) were used. Disease activity and patient-reported outcomes were compared in male and female patients, and the predictors of MDA for both genders were analyzed. Results: The patients' mean age was 47.6 years (SD: 12) for females and 46.3 years (SD: 12.3) for males. In terms of DAS28 and cDAPSA, female patients had significantly higher disease activity scores, while male patients had significantly higher remission rates (P<0.05). There was a significant difference in the rate of MDA in favor of males (P<0.05), but not in VLDA. The incidences of dactylitis, enthesitis, tenosynovitis, and inflammatory bowel disease were similar in male and female patients, except for spondylitis, which was higher in males (P<0.05). Overall, although there was no significant between-group difference in age and disease duration, female patients had significantly higher BMI and late-onset disease (P<0.05). Female patients had higher HAD, HAQ, and FiRST and lower SF-36 scores than males (P<0.05). In both male and female patients, the disease activity score of cDAPSA was significantly correlated with the scores of FiRST, HAD, VAS-F, and HAQ(P< 0.05). In regression analysis, tender joint count, swollen joint count, PASI, pain VAS, and enthesitis were the MDA predictors in both genders. Conclusion: In patients with peripheral PsA, males are more likely to develop spondylitis while other extraarticular manifestations are similar. Female patients appear to have lower rates of remission and MDA and higher levels of disease activity. Female patients experience a more severe course of PsA, with higher levels of pain and fatigue, lower quality of life, and increased functional limitations. The predictors of MDA, i.e., tender joint count, swollen joint count, PASI, pain VAS, and enthesitis are similar between the two genders. (C) 2021 Societe francaise de rhumatologie. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Psoriatic arthritis; Gender characteristics; Sex; Women's health; PREVALENCE; POPULATION; DEPRESSION; REMISSION; CRITERIA; FATIGUE; ANXIETY; IMPACT